Analisis Deiksis Bahasa Kutai di Kecamatan Muara Muntai Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Rosita, Rosita; Hefni, Asnan; Sulistyowati, Endang Dwi (Universitas Mulawarman, 2019)
This research aims to describe the type, shape, and function of the cyclical deiksis of Kutai language in Muara Muntai District of East Kalimantan Province. Data analysis techniques are organized in several steps, namely data reduction, data presentation, and conclusion withdrawal. Based on the results of data analysis, it was found that the type of cyclical system of Kutai language consists of persona deiksis, place decission, and time decisity. The decyclical form of Kutai language persona is divided into three, namely the first pronomina that refers to oneself, the second pronoun that refers to the speaker to the interlocutor, and the third pronoun that is the person being talked about. A form of place decisis as a gift of form to a place in a language event. The form of decyclical time giving the form of expression time is done in speech. The function of decises is divided into three, namely, the function of decission persona includes as a pointer to belong, as the subject, as an object, is a function that is found in many studies. The decyclical function where use in research leads a lot as a place description indicator. The decyclical function of time in this study shows the description of time.